2021
DOI: 10.3934/gf.2021013
|View full text |Cite
|
Sign up to set email alerts
|

Mobile banking during COVID-19 pandemic in Bangladesh: A novel mechanism to change and accelerate people's financial access

Abstract: <abstract> <p>Limited access to financial services is considered as a vital bottleneck for curbing poverty in Bangladesh. Digital technology such as mobile banking can contribute to accelerate people's access to finance but did not receive proper attention before COVID-19. This study intends to explore the use of mobile banking services to accelerate people's financial access in Bangladesh due to the emergence of the COVID-19 pandemic by using secondary data. Mainly documentation techniques and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Besides, FinTech provides the financial sector and the public in making their daily transactions more affordable, convenient, and secure (Chen et al 2019 ; Puschmann 2017 ). The use of technologies has been accelerated by the COVID-19 in virtually all areas of the world (Al Nawayseh 2020 ; Khatun et al 2021 ). Financial experts predict that the epidemic has accelerated the adoption of digital banking systems by 3 to 10 years (Reich 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, FinTech provides the financial sector and the public in making their daily transactions more affordable, convenient, and secure (Chen et al 2019 ; Puschmann 2017 ). The use of technologies has been accelerated by the COVID-19 in virtually all areas of the world (Al Nawayseh 2020 ; Khatun et al 2021 ). Financial experts predict that the epidemic has accelerated the adoption of digital banking systems by 3 to 10 years (Reich 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, mobile technology proved critical in maintaining a germ-free environment, and it is still effective and useful in the post-COVID-19 era (Sharifi et al 2021 ). In this regard, the COVID-19 outbreak may also have expedited the use of FinTech platforms such as mobile banking services in developing economies like Bangladesh (Khatun et al 2021 ). Mobile Financial Services (MFS) are banking services mediated by mobile networks, thus enabling customers to conduct banking and other financial transactions using their mobile phones (Azad 2016 ; Biswas 2021 ; Khatun et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Khatun et al (2021), which explored the use of mobile banking services to accelerate people's financial access in Bangladesh due to the emergence of the COVID-19 pandemic, pointed to the fact that the number of registered mobile banking customers has escalated. In the article, the authors showed that mainly government policies regarding different mobile banking transactions such as cash in, cash out, person to person (P2P) transaction, salary and utility bill payments, etc., have significantly increased the people's digital financial access during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%